Designing Inhibitors for the SARS CoV Main Protease as Anti-SARS Drugs - Bari, Hamza; Awan, Arif Ali (McGill Journal of Medicine, 2020)
Severe Acute Respiratory Syndrome (SARS) is a serious respiratory illness reported in parts of Asia and Canada. A novel coronavirus (CoV) has been isolated and identified as the cause of the SARS for which there is currently no effective treatment. Given the epidemic, the rapid development of efficacious antiviral drugs is needed. The key replicative enzyme SARS CoV main protease (Mpro) represents an attractive target for antiviral chemotherapy. Detailed structural study of the substrate binding cavity led to the generation of a 3-D pharmacophore. Subsets of chemical structures were extracted from the commercial databases by using the defined pharmacophore. Compound mapping to the pharmacophore were docked into the substrate-binding cavity and scored. The selected chemicals were assayed against the SARS CoV Mpro for their inhibitory activity. Three of the compounds showed significant inhibition of the SARS CoV Mpro at low micromolar concentration. This study provides potential lead compounds for specific SARS CoV protease inhibitors. It also signifies the utility of computational techniques for rapid discovery of inhibitors for novel targets.